Tobacco-specific nitrosamine exposure from electronic cigarettes versus combustible cigarettes: an ad hoc analysis within a systematic review of emission studies - Miguel, Red Thaddeus D.; Ali, Rami; El Joumaa, Manal (Frontiers in Oncology, 2025)
IntroductionTobacco-specific nitrosamines (TSNAs), particularly 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N′-nitrosonornicotine (NNN), have been shown to be among the most potent carcinogens found in tobacco products. With the rapid adoption of electronic cigarettes (e-cigarettes) as alternatives to combustible cigarettes, understanding the extent of TSNA exposure has become central to oncology practice and risk communication.MethodsThis ad hoc analysis, based on studies identified from a systematic review of e-cigarette emissions, synthesized evidence from 13 emission studies that directly compared NNK and NNN levels between e-cigarette aerosols and cigarette smoke. Eligible studies were identified through comprehensive database searches (MEDLINE, Embase, and ToxFile) and assessed for methodological rigor using an adapted QualSyst framework.ResultsAcross studies, validated analytical methods, primarily LCMS/MS and UPLC-MS, demonstrated that TSNAs in e-cigarette aerosols were either undetectable or present at concentrations lower than those in combustible cigarette smoke, with reductions typically exceeding 99%. The findings show a toxicological difference between combustible cigarettes and e-cigarettes, with the latter exhibiting substantially reduced TSNA emissions comparable to laboratory background air levels.DiscussionThese results suggest that switching to exclusive e-cigarette use can lead to a significant reduction in exposure to key tobacco-specific nitrosamines. This study also reinforces the importance of articulating this evidence with clarity, precision, and balance, recognizing both the substantial benefits of reduced exposure and the residual uncertainties that only long-term studies will resolve.